2008
DOI: 10.1126/science.1159023
|View full text |Cite
|
Sign up to set email alerts
|

A Conserved Mutation in an Ethylene Biosynthesis Enzyme Leads to Andromonoecy in Melons

Abstract: Andromonoecy is a widespread sexual system in angiosperms characterized by plants carrying both male and bisexual flowers. In melon, this sexual form is controlled by the identity of the alleles at the andromonoecious (a) locus. Cloning of the a gene reveals that andromonoecy results from a mutation in the active site of 1-aminocyclopropane-1-carboxylic acid synthase. Expression of the active enzyme inhibits the development of the male organs and is not required for carpel development. A causal single-nucleoti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

16
308
0
9

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 331 publications
(333 citation statements)
references
References 20 publications
16
308
0
9
Order By: Relevance
“…In contrast to gynodioecy, the underlying genetics of the monoecy pathway are only starting to be understood (Boualem et al, 2008;Martin et al, 2009). However, phenotypic models have shown that unisexual individuals can invade a monoecious population if the investment in one sexual function, particularly the male function, provides increasing fitness returns (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to gynodioecy, the underlying genetics of the monoecy pathway are only starting to be understood (Boualem et al, 2008;Martin et al, 2009). However, phenotypic models have shown that unisexual individuals can invade a monoecious population if the investment in one sexual function, particularly the male function, provides increasing fitness returns (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Several investigations have shown that phytohormones are involved in changes of flower type, number and ratio of flowers of different sex types, modifications of flowering time and of other traits related to sex expression (Noguera et al 2005, Papadopoulou et al 2005, Stankovic et al 2005, Yamasaki et al 2005, Little et al 2007, Boualem et al 2008, Ouzounidou et al 2008, Martin et al 2009). Most of these studies were performed in cucumber, the model plant for studying sex expression in Cucurbitaceae.…”
Section: Introductionmentioning
confidence: 99%
“…Cucurbits are becoming primary models for the study of several biological processes (Boualem et al 2008;Ezura and Fukino 2009;Li et al 2009). The availability of molecular tools, including the whole genome sequence, has significantly increased in the last years, mainly for melon and cucumber (Huang et al 2009;Gonzalez et al 2010), but more recently also for the Cucurbita genus.…”
Section: Introductionmentioning
confidence: 99%